Towards the identification of new biomarkers in saliva and erum for treatment monitoring of equine gastric ulcer syndrome: a liquid proteomic approach - Muñoz Prieto, Alberto; Rubić, Ivana; Rešetar Maslov, Dina; González Sánchez, Juan Carlos; Mrljak, Vladimir; Cerón, Jose Joaquín; Hansen, Sanni (Animals, 2024)
Equine gastric ulcer syndrome (EGUS) is a common condition in horses. This study explores the use of liquid proteomics to identify new biomarkers in saliva and serum to monitor EGUS treatment. The proteomes of horses with EGUS before and after a successful treatment with omeprazole were analysed. In saliva, 503 proteins were identified, with 7 upregulated and 6 downregulated post-treatment. Among the proteins that changed, there was an increase in vimentin, linked to wound healing, and a decrease in podocalyxin, associated with tissue damage. In serum, 206 proteins were found, with significant changes in 5. Keratin type I increased, supporting epithelial integrity, whereas immunoglobulin lambda decreased, indicating a reduced immune response. Gene ontology analysis revealed a decrease in immune-related pathways after successful treatment. Overall, 13 proteins in saliva and 5 in serum showed significant changes after treatment, highlighting the differential responses of saliva and serum in EGUS. This report creates new avenues for discovering potential biomarkers to monitor EGUS treatment, which is of high importance for the management of this prevalent disease.
Online veröffentlicht: 28. Oktober 2024
Gesehen am 25.06.2025